Atomic Structure and Morphology of Fumed Silica - Myronyuk, I. F.; Kotsyubynsky, V. O.; Dmytrotsa, T. V.; Soltys, L. M.; Gun’ko, V. M. (Physics and Chemistry of Solid State, 2020)
The comparative analysis of atomic structure and morphology of fumed silica nanoparticles prepared under different synthesis conditions are studied using TEM, FTIR, quantum chemistry, and low-temperature nitrogen adsorption methods. It was determined that the structure of amorphous silica nanoparticles is formed by branched chain-like clusters of the length of 0.6-2.4 nm that correspond to proto-particles or nuclei of nanoparticles. A linear part of the smallest clusters is consisted of two tetrahedra SiO4 with common oxygen atom and oppositely directed vertices. The inter-tetrahedral average angle of Si ‒ O ‒ Si bonds is about 180˚. It is shown that textural porosity of fumed silica powder depends on the initial degree of aggregation of nanoparticles. The average mesopores (1 nm < R < 25 nm) volume is in the rage of 0.26-0.60 cm3∙g-1 for materials pretreated at different temperatures. It is found out that the mean mesopores radius decreases from 34 nm to 10 nm with decreasing average size of silica nanoparticles. The micropores (R < 1 nm) contribution to the total pore volumes is small for all materials (0.003-0.029 cm3∙g-1).